2020
DOI: 10.1097/ico.0000000000002403
|View full text |Cite
|
Sign up to set email alerts
|

Topography-Guided Photorefractive Keratectomy for Postkeratoplasty Astigmatism: Long-Term Outcomes

Abstract: Purpose: To evaluate the long-term efficacy and safety of topography-guided photorefractive keratectomy (TG-PRK) for postkeratoplasty refractive error correction. Methods: A retrospective interventional case series of 54 eyes of 50 patients who underwent previous corneal transplants. Unaided distance visual acuity (UDVA) and best corrected visual acuity (CDVA), manifest refraction, mean central keratometric value, mean keratometric astigmatism, and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The significant improvement of UDVA is supported by previous case series or retrospective studies using the same surgical technique. 11 , 31 However, final UDVA values between studies are hardly comparable due to the different refractive characteristics at enrollment, where our patients presented higher values of SRAST, SimK, and SEQ and worse UDVA and CDVA at T0. Consequently, when comparing between studies mean UDVA values at the final follow-up, our cohort obtained a worse visual acuity without the use of spectacles; conversely, when comparing UDVA changes, the observation of a mean improvement of 5.67±2.93 lines in our study is consistent with previous literature and in some cases even more conspicuous.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The significant improvement of UDVA is supported by previous case series or retrospective studies using the same surgical technique. 11 , 31 However, final UDVA values between studies are hardly comparable due to the different refractive characteristics at enrollment, where our patients presented higher values of SRAST, SimK, and SEQ and worse UDVA and CDVA at T0. Consequently, when comparing between studies mean UDVA values at the final follow-up, our cohort obtained a worse visual acuity without the use of spectacles; conversely, when comparing UDVA changes, the observation of a mean improvement of 5.67±2.93 lines in our study is consistent with previous literature and in some cases even more conspicuous.…”
Section: Discussionmentioning
confidence: 68%
“…Consequently, when comparing between studies mean UDVA values at the final follow-up, our cohort obtained a worse visual acuity without the use of spectacles; conversely, when comparing UDVA changes, the observation of a mean improvement of 5.67±2.93 lines in our study is consistent with previous literature and in some cases even more conspicuous. 14 , 31 In addition, it should be noted that our patients were selected among those who were intolerant to spectacles and/or CLs, and not among those who were likely to reach emmetropia. However, the significant improvement of CDVA is consistent with Sorkin et al 29 probably due to highly irregular astigmatism (mean >6D) at enrollment, which could have curtailed the effect of the correction with spectacles or CLs before intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HOAs (mean SA and mean coma) significantly reduced at the 6-month visit. Sorkin et al 10 found a statistically significant improvement in the analyzed aberration parameters measured including total RMS, HOA RMS, defocus, coma, trefoil, and spherical aberration in 13 eyes.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have demonstrated the effectiveness in TG-treatments for the treatment of corneal irregular astigmatism 2–6 , 8 , 10–14 , 17–21 with most of these being done in patients with irregular astigmatism secondary to keratoplasty, RK or post-refractive decentered/small zone ablations. Lains et al 20 reported a retrospective case series of 31 eyes with irregular astigmatism after PKP treated with TG-PRK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation